THE INFLUENCE OF WATER-SOLUBLE SALTS ON THE MOISTURE CONDITION IN THE EXTERIOR PACKAGING STRUCTURES OF INDUSTRIAL ENTERPRISES - Qodirov Giyozjon Mirzajonovich (Journals Park Publishing, 2022)
This article presents the work done on the calculation of the moisture condition of packing structures under the influence of salts, the vapor permeability and sorption processes in various chemical compositions and structures of salt solutions.
Keywords: closed constructions, types, properties, physical, chemical and biological processes